2012
DOI: 10.1093/carcin/bgs158
|View full text |Cite
|
Sign up to set email alerts
|

Meat-related mutagen exposure, xenobiotic metabolizing gene polymorphisms and the risk of advanced colorectal adenoma and cancer

Abstract: Meat mutagens, including heterocyclic amines (HCAs), polycyclic aromatic hydrocarbons (PAHs) and N-nitroso compounds (NOCs), may be involved in colorectal carcinogenesis depending on their activation or detoxification by phase I and II xenobiotic metabolizing enzymes (XME). Using unconditional logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CI), we examined the intake of five meat mutagens and >300 single nucleotide polymorphisms (SNPs) in 18 XME genes in relation to advanced col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…Specifically, few studies have investigated the modifying effects of this comprehensive subset of polymorphisms on the HAA/meat mutagenicity-colorectal adenoma associations. Five studies with varied overlap in the genetic factors of interest were identified but none investigated CYP1B1*2 or XPD polymorphisms (Barbir et al 2012;Gilsing et al 2012;Lilla et al 2006;Tiemersma et al 2004;Wang et al 2011c).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, few studies have investigated the modifying effects of this comprehensive subset of polymorphisms on the HAA/meat mutagenicity-colorectal adenoma associations. Five studies with varied overlap in the genetic factors of interest were identified but none investigated CYP1B1*2 or XPD polymorphisms (Barbir et al 2012;Gilsing et al 2012;Lilla et al 2006;Tiemersma et al 2004;Wang et al 2011c).…”
Section: Discussionmentioning
confidence: 99%
“…HCA-specific DNA adducts have also been detected in some specimens of human colon tissue samples, suggesting that HCA exposure may also be related to human cancer risk (11,12), but epidemiologic data for HCA intake and colorectal neoplasia in humans are inconsistent. Higher intake of total or type-specific HCA estimated from cooked meat and fish was associated with increased risk of colorectal cancer or its precursor colorectal adenoma in some U.S. (13)(14)(15)(16)(17) and European studies (18,19), but not others (20)(21)(22)(23). A Swedish study found no association between overall HCA intake and colon or rectal cancer but suggested carcinogenic potential at extreme high intake (24).…”
Section: Introductionmentioning
confidence: 99%
“…One article was subsequently excluded because it did not met the inclusion criteria since estimated the exposure to HCAs (low, intermediate and high) on the base of red meat source and preparation but not give their concentrations. Therefore, at the end of the selection process, 39 studies which met the inclusion criteria were enclosed in the systematic review and meta-analysis (Figure 1), 17 on CRA [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], 20 on CRC [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66], and 2 studies reported data on both CRA and CRC [67,68]. …”
Section: Resultsmentioning
confidence: 99%
“…Case-control studies were published between 2001 and 2015, 12 were population-based [31,32,35,37,39,40,[42][43][44]46,67,68] and 3 were hospital-based [30,33,45]. Twelve were conducted in the United States [30][31][32][33]35,37,39,40,42,44,67,68] and one each in Europe [43], Canada [45] and Japan [46].…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation